Influence of Ca- and Al-additives on the pollutant emissions from blends of wood and straw in small-scale combustion. (July 2021) - Höfer, Isabel; Huelsmann, Theresa; Kaltschmitt, Martin
Abstract: In the last few years, biomass has become increasingly important as a constantly available, renewable and CO2 -neutral energy carrier. A growing sector is the combustion of biomass in small-scale combustion plants (<100 kW). If the growth of this sector continues, there may be a shortage of the resource biomass in the future. Another challenge related to biomass combustion is the clearly higher release of total particulate matter (tPM) emissions due to the higher content of aerosol forming elements in biomass fuels (especially the content of potassium) compared to fossil fuels like oil and gas. Thus, the threshold values especially for such airborne pollutants released from biomass combustion, especially wood, in small-scale combustion plants are being tightened more and more. Therefore, the aim of the present work is to investigate the influence of the additive CaHPO4, in comparison of the well-known additive kaolin (amount of 0.5 wt%), on the pollutant formation (tPM and CO) of beech wood and blends of beech wood and barley straw (with a proportion of up to 20 wt%) during combustion in a small-scale combustion plant (8 kW). The measurements show considerable reduction effects of both additives for the CO and total PM emissions. For example, the total PM emissions of the pure wood sample can be reduced with the additive kaolin by about 60%. For the blends of wood and straw the additive CaHPO4 shows an effective reduction effect of 50% (10 wt% straw/90 wt% wood) and of 40% (20 wt% straw/80 wt% wood). By contrast, a significant reduction of more than 50% of CO emissions can be achieved in all samples with the help of the additive kaolin. Highlights: Significant reduction > 50% of CO emissions by kaolin. Total PM emissions of wood sample reduced with additive kaolin by 60%. For wood-straw blends additive CaHPO4 effective PM reduction of 40–50%. Blends with 0.5 wt% CaHPO4 have similar or lower emissions of PM than wood sample.